أسباب السلوك العدواني لدى تلاميذ الطور المتوسط من وجهة نظر الأساتذة (دراسة عدد حالات بمتوسطة العمري السايح بالأغواط) - حمزة ديمح; علي عون (My University, 2021)
This study aimed to find out more about the causes of aggressive behavior of middle school students from the teachers' point of view. For the purposes of this study, a questionnaire method was used to collect the required information, as it was distributed to an accessible sample whose vocabulary was 3 students, whose behavior was noted as aggressive, within the Omari Al-Sayeh middle school in Laghouat. The data was analyzed based on tables and extracting percentages from the total percentage of the sample. The study concluded a number of results, the most important of which are: The proportion of male students is higher than females, but it is close. Half of the sample is in the middle of the third level average. More than half of the sample live in a large family, and they live in a good social and moderate economic situation. A small percentage of the sample confirms that their aggressive behavior is female. Half of the sample have a good relationship with their teachers, and they sometimes threaten the people around them Middle school students - aggressive behaviour